Toward an Understanding of the Perpetuation of the Agent of Tularemia - Telford, Sam; Goethert, heidi (Frontiers in Microbiology, 2011)
The epidemiology of tularemia has influenced, perhaps incorrectly skewed, our views on the ecology of the agent of tularemia. In particular, the central role of lagomorphs needs to be reexamined. Diverse observations, some incidental, and some that are more generally reproducible, have not been synthesized so that the critical elements of the perpetuation of Francisella tularensis can be identified. Developing a quantitative model of the basic reproduction number (BRN) of F. tularensis may require separate treatments for Type A and Type B given the fundamental differences in their ecology.